Staphylococcus aureus Alpha-Toxin Disrupts Endothelial-Cell Tight Junctions via Acid Sphingomyelinase and Ceramide - Becker, Katrin Anne (Infect Immun, 2017)
Staphylococcus aureus (S. aureus) infections are among the most common and severe infections, garnering notoriety in an era of increasing resistance to antibiotics. It is therefore important to define molecular mechanisms by which this pathogen attacks host cells. Here, we demonstrate that alpha-toxin, one of the major toxins of S. aureus, induces activation of acid sphingomyelinase and concomitant release of ceramide in endothelial cells treated with the toxin. Activation of acid sphingomyelinase by alpha-toxin is mediated via ADAM10. Infection experiments employing alpha-toxin-deficient S. aureus and the corresponding wild-type strain reveal that activation of acid sphingomyelinase in endothelial cells requires alpha-toxin expression by the pathogen. Activation of acid sphingomyelinase is linked to degradation of tight junctions in endothelial cells in vitro, which is blocked by pharmacological inhibition of acid sphingomyelinase. Most importantly, alpha-toxin induces severe degradation of tight junctions in the lung and causes lung edema in vivo, which is prevented by genetic deficiency of acid sphingomyelinase. These data indicate a novel and important role of the acid sphingomyelinase/ceramide system for the endothelial response to toxins and provide a molecular link between alpha-toxin and the degradation of tight junctions. The data also suggest that inhibition of acid sphingomyelinase may provide a novel treatment option to prevent lung edema caused by S. aureus alpha-toxin.